Experimental demonstration of ultrasensitive sensing with terahertz metamaterial absorbers: A comparison with the metasurfaces - Cong, Longqing (2015)
Planar metasurfaces and plasmonic resonators have shown great promise for sensing applications across the electromagnetic domain ranging from the microwaves to the optical frequencies. However, these sensors suffer from lower figure of merit and sensitivity due to the radiative and the non-radiative loss channels in the plasmonic metamaterial systems. We demonstrate a metamaterial absorber based ultrasensitive sensing scheme at the terahertz frequencies with significantly enhanced sensitivity and an order of magnitude higher figure of merit compared to planar metasurfaces. Magnetic and electric resonant field enhancement in the impedance matched absorber cavity enables stronger interaction with the dielectric analyte. This finding opens up opportunities for perfect metamaterial absorbers to be applied as efficient sensors in the finger print region of the electromagnetic spectrum with several organic, explosive, and bio-molecules that have unique spectral signature at the terahertz frequencies.